Results of biochemical and histological studies after restoration of bone defects using cellular technologies in dental patients - Bambuliak, A.V.; Kuzniak , N.B.; Lopushniak , L.Y.; Dronyk І.І.; Myhal, O.O. (Medicni Perspektivi, 2024)
Objective of the research was to find out the effectiveness of the use of osteoplastic materials based on the multipotent mesenchymal stromal cells of the adipose tissue during surgical treatment for restoration of bone defects in dental patients. The clinical material included examination of 79 patients who underwent replacement of bone defects of the alveolar processes and/or an alveolar part of the appropriate jaw by means of different osteoplastic materials and their combinations or without their application (the control group). Acid phosphatase activity in the oral fluid of patients was determined by means of the unified “end point” method. Alkaline phosphatase activity in the oral fluid was determined using a set of reagents produced by the company “Filisit-Diagnostika” (Ukraine). Oral fluid mineralization index (MI) of patients was calculated according to the ratio of enzymatic activity of alkaline phosphatase (ALP) to acid phosphatase (AP) according to the formula: MI=ALP/AP. Histological material was taken at the stage of installation of a dental implant. It was established that the use of a composition based on multipotent mesenchymal stromal cells of adipose tissue, platelet-enriched blood plasma and bone tissue substitute containing hydroxyapatite contributes to the improvement of regenerative processes in the bone tissue of the jaws, which is confirmed by a 28.68% decrease in acid phosphatase activity, an increase by 25, 97% of alkaline phosphatase activity in the oral fluid of group B patients and, accordingly, a 77.08% increase in the ratio of alkaline to acid phosphatase. According to the results of histological studies and phase-contrast microscopy, after 6-8 months of observation, in patients of group B, the areas of jaw defects were filled with newly formed bone tissue, identical to native bone, and the resulting trepanobioptas had the structure of cancellous bone with osteoblastic elements forming a chain around osteoid tissue. Having analyzed the results of biochemical and histological studies it was established that application of an osteoplastic composition based on the multipotent mesenchymal stromal cells of the adipose tissue, bone tissue substitute with hydroxyapatite and platelet-rich plasma allows restoration of bone defects of the alveolar processes and an alveolar part of the appropriate jaw in shorter terms. The method is an optimal alternative to traditional osteoplastic materials to be used in modern dental practice and dental implantation.